Ectoparasites of brown rats (Rattus norvegicus) in Grenada, West Indies - Thille, Katelyn Noelle (Vet World, 2019)
BACKGROUND AND AIM: Arthropod ectoparasites (mites, lice, ticks, and fleas) on common house rats or brown rats (Rattus norvegicus) are known to transmit zoonotic pathogens and diminish rat health. To the best of our knowledge, there is no published information regarding the prevalence of ectoparasites on R. norvegicus in Grenada. This study aimed to determine the prevalence and types of ectoparasites present on brown rats from Grenada. MATERIALS AND METHODS: One hundred sixty-eight rats were collected live from the parishes of St. George and St. David, Grenada, from May to July 2017. Following euthanasia, external parasites were collected using fine combs, thumb forceps, and paper tape. Tape samples and free specimens were placed in containers with 70% ethanol. External parasites were evaluated using dissection microscopy. RESULTS: Over 2000 ectoparasites were collected from 149 of the 168 trapped rats (88.7%). Ectoparasites identified included mesostigmatid mites (found on 84.6% of infested rats), fur mites in the families Atopomelidae and Listrophoridae (67.1%), Polyplax spp. lice (6.7%), fleas (3.4%), an unidentified larval tick (0.7%), and a mite in the family Myobiidae (0.7%). Infestation rates were higher in St. David Parish (86/89; 96.6%) than in St. George Parish (63/79; 79.7%) (p=0.001). When comparing sex and age, males had a marginal increase in infestation rate (83/89; 93.3%) compared to females (66/79; 83.5%) (p=0.054), and adults had an infestation rate of 90.7% (97/107) compared to juvenile rats who had a 66.7% (14/21) infestation rate. CONCLUSION: Brown rats in Grenada are heavily infested with ectoparasites, including known vectors of pathogens. Future studies will examine the prevalence of zoonotic pathogens in these arthropods.